Opuntia delafuentiana (Cactaceae: Opuntioideae), a new xoconostle from central Mexico - Martínez-González, Cesar Ramiro; Luna-Vega, Isolda; Gallegos-Vázquez, Clemente; García-Sandoval, Ricardo (Phytotaxa, 2015)
We describe a new species of a wild Mexican Opuntia producer of edible acidic prickly pears (xoconostles), locally known as “xoconostle de cerro blanco“ (white hillside xoconostle), based on external morphology and micromorphology attributes (mainly characters of the spines). This species is morphologically compared with another four species of wild xoconostles distributed in the same region: O. joconostle, O. leiascheinvariana, O. oligacantha and O. matudae. A taxonomic key for the xoconostles of the area is provided. Based on the phylogenetic analysis of one chloroplast gene, one plastid intergenic spacer and one nuclear molecular marker, the new species was recognized as a monophyletic group within Opuntia s.s. sensu Majure et al.